Influence of fertilizers on contents, fractional structure and balance of humus in sod-podsolic soil of the North - N. T. Chebotaryov; A. A. Yudin; A. V. Oblizov (Аграрная наука Евро-Северо-Востока, 2016)
Researches on studying of efficiency of organic (40 and 80 t/ha of TNK) and mineral fertilizers (73 NPK, NPK and 1 NPK), and their combining use on a humic state, group and fractional structure, and balance of a humus of the sod-podsolic middle-cultivated sandy loam soil were conducted in field stationary experiment in a fodder crop rotation. As a result of the carried out researches it is established that the greatest positive balance of humus is received at use of organic fertilizers (0.41-1.80 t/ha on average per year), and also their joint use with mineral fertilizers (0.50.0.63; 1.96.2.10 t/ha); the greatest values are received at application of high dose of TNK and NPK (1.96-2.10 t/ha). Studying of group and fractional structure of a humus has shown that organic and mineral fertilizers, especially at their joint use promoted increase of content of the most valuable fraction of humic acids (GK-2) from 2.3 to 5.2% and to decrease in the most aggressive fraction of fulvic acids (FC-1a) from 3.5 to 2.7%. In general, fertilizers, especially in high doses, promoted increase of humus quality (from gumate-fulvatic type it has passed into fulvatic-gumate type). Ratio Cga: Cfa has made 1.30-1.33; in variants with mineral fertilizers and joint input of organic and mineral fertilizers (TNK in dose 40 t/ha + NPK) - 1.22-1.27; in variant without fertilizers - 0.98.